2020
DOI: 10.1136/injuryprev-2020-043831
|View full text |Cite
|
Sign up to set email alerts
|

Changes in intimate partner violence during the early stages of the COVID-19 pandemic in the USA

Abstract: The objective of this study is to describe intimate partner violence (IPV) severity and types of victimization during the early states of the COVID19 pandemic. A survey was distributed through social media and email distribution lists. The survey was open for 14 days in April 2020 and 2441 participated. Information on IPV, COVID19-related IPV severity, sociodemographics, and COVID19-related behaviors (eg, job loss) were collected. Regression models were used to evaluate COVID19-related IPV severity across vict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
156
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(171 citation statements)
references
References 11 publications
11
156
3
1
Order By: Relevance
“…While the number of cases was small, there was a statistically significant increase in the proportion of cases reporting psychological or emotional abuse, from 11.69% (8 cases) in 2018 to 28.57% (9 cases) in 2020. This finding is similar to an online survey of 2441 respondents conducted in the USA that found that 18% of respondents had experienced intimate partner violence since COVID-19, with the most common form being emotional or psychological abuse [39]. Emotional or psychological abuse is priority issues in child maltreatment cases; however, it is often a neglected component of adult domestic violence and sexual assault cases [40], which often focuses on physical trauma or circumstances that meet criminal thresholds [41].…”
Section: Discussionsupporting
confidence: 78%
“…While the number of cases was small, there was a statistically significant increase in the proportion of cases reporting psychological or emotional abuse, from 11.69% (8 cases) in 2018 to 28.57% (9 cases) in 2020. This finding is similar to an online survey of 2441 respondents conducted in the USA that found that 18% of respondents had experienced intimate partner violence since COVID-19, with the most common form being emotional or psychological abuse [39]. Emotional or psychological abuse is priority issues in child maltreatment cases; however, it is often a neglected component of adult domestic violence and sexual assault cases [40], which often focuses on physical trauma or circumstances that meet criminal thresholds [41].…”
Section: Discussionsupporting
confidence: 78%
“…Following the lead of previous reviews, also in our work we found a sharp spike in DV cases reported around the globe (Agüero 2020; Baig et al 2020;Barbara et al 2020;Boserup et al 2020;Bradley et al 2020;Chandan et al 2020;Gebrewahd et al 2020;Ghoshal et al 2020;Goh et al 2020;Gosangi et al 2020;Jarnecke et al 2020;Jetelina et al 2020;Kaukinen et al 2020;Kofman et al 2020;Kumar 2020;Leslie et al 2020;Mahase et al 2020;Mazza et al 2020;Neil 2020;Nigam 2020;Piquero et al 2020;Qin et al 2020;Roesch et al 2020;Roseboom et al 2020;Sifat 2020;Telles et al 2020;Tochie et al 2020;Vieira et al 2020;Yahya et al 2020;Zargham et al 2020). For example, Aguero (2020) in a study conducted in Peru, one of the several countries which imposed a national lockdown in March, found that the incidence rate of calls to helplines centres increased around 48% between April and July 2020.…”
Section: Resultssupporting
confidence: 81%
“…The current study focused on lower levels of relationship conflict that may precede or exacerbate more serious forms of conflict. Recent studies raise concerns about increasing victimization among IPV victims (Jetelina et al, 2020), whether police are responding adequately to increased IPV calls (Bullinger et al, 2020), and increasing severity of IPV injuries (Gosangi et al, 2020). Thus, one implication is the need to ensure effective intervention and response how to IPV during social distancing and stay-at-home orders.…”
Section: Implications For Policy Practice and Interventionmentioning
confidence: 99%